Carbon Nanotube Reinforced Poly‐p‐Phenylene Terephthalamide Fibers for Toughness Improvement: A Molecular Dynamics Study. Issue 10 (6th September 2020) - Mao, Zebei; Li, Tong; Zhang, Ke; Li, Dongyu; Zhou, Caihua; Ren, Mingfa; Gu, Yuantong; Wang, Bo
Abstract: Poly‐ p ‐phenylene terephthalamide (PPTA) fibers, such as DuPont's Kevlar fiber, are widely used in various fiber‐reinforced composites due to their outstanding tensile stiffness, strength, and energy absorption capacity. To further improve the strength of PPTA‐based fibers, it is necessary to investigate the molecular deformation mechanisms of these fibers while being coupled with nanoreinforcements. In this work, molecular dynamics method is used to predict the mechanical performance of carbon nanotubes (CNTs) reinforced Kevlar fibers, based on the molecular modeling of crystal interfaces in the microstructure of Kevlar fiber with the help of surface‐modified CNTs, the tensile strength of Kevlar fibers can be increased by 27.8–39.7%. Furthermore, the mechanism of binding stability of CNTs is investigated by modifying the functional groups of CNTs, in which the hydrogen bonds (H‐bonds) interaction plays an important role. Abstract : Based on the molecular modeling technique, the author predicts that the tensile strength of Kevlar fibers can be increased by 27.8–39.7% by carefully introducing carbon nanotube (CNT) reinforcements. The binding stability of CNTs in the poly‐ p ‐phenylene terephthalamide fibers is investigated by modifying the surface functional groups of CNTs, in which the H‐bond interaction plays a critical role.